Safety and Efficacy of an Atraumatic Uterine Cervical Traction Device: A Pilot Study - Legardeur, Hélène; Masiello-Fonjallaz, Gessica; Jacot-Guillarmod, Martine; Mathevet, Patrice (Frontiers in Medicine, 2021)
Introduction Alignment of the uterine cervix with the vaginal canal is often required during insertion of an intrauterine contraceptive device (IUD). Currently available instruments are traumatic tenacula, which can cause pain and bleeding and represent an obstacle for certain patients to pursue their medical follow-up. A novel investigational cervical vacuum tenaculum, enables atraumatic traction of the cervix using a semi-circular suction pad, designed to conform to the anatomical shape of the external cervical os. Suction is generated by manually pulling out a sliding tube in a vacuum chamber. Methods We performed a single arm non-comparative pilot study to assess the safety and efficacy of the cervical vacuum tenaculum in 13 women receiving an IUD. Data on procedural efficacy, safety, patient-reported pain scores at specific time points during IUD insertion procedure and patient satisfaction were collected prospectively. Results Insertion of IUD was successful with use of the study device in 7 of the 13 enrolled patients (54%). No bleeding or only limited ecchymosis were caused by the device. No adverse events were reported. Participants reported very little pain (mean Visual Analogue Scale <10) when applying the device. Participants who achieved IUD insertion with the device reported strong overall satisfaction with the procedure. Conclusions The suction-based atraumatic tenaculum can be used to manipulate the cervix during IUD insertion with satisfactory efficacy and safety. The results of this pilot study support further studies of this device in larger populations comparing with standard single-tooth tenaculum.